Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1002/admi.202201080
|View full text |Cite
|
Sign up to set email alerts
|

Smooth Transparent Omniphobic Coatings with Remarkable Liquid Repellence

Abstract: leaf (Nelumbo), superhydrophobic surfaces with a contact angle > 150° and low roll-off angles < 10°, have shown remarkable properties such as selfcleaning (so-called lotus effect), [1,2] antibiofouling [3] and anti-corrosion. [10,11] The surfaces rely on air pockets trapped in the micro-/nano-hierarchical structures to diminish the contact between the surface and the liquid to be repelled (Cassie-Baxter state). However, the composite solid/air interface design of these surfaces is metastable. Extreme condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 50 publications
(84 reference statements)
0
4
0
Order By: Relevance
“…Fluorinated monomers with four or six fluorinated carbons in the side chain are replaced with C8‐based fluorinated monomers. However, fluorinated fluoroalkyl groups with shorter side chains are less crystalline, and thus exhibit higher surface molecular mobility 35,38,39 . Consequently, carbonyl groups (–COO–), which are polar groups in fluoroalkyl groups, are exposed on the surface when in contact with water 35,36 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluorinated monomers with four or six fluorinated carbons in the side chain are replaced with C8‐based fluorinated monomers. However, fluorinated fluoroalkyl groups with shorter side chains are less crystalline, and thus exhibit higher surface molecular mobility 35,38,39 . Consequently, carbonyl groups (–COO–), which are polar groups in fluoroalkyl groups, are exposed on the surface when in contact with water 35,36 .…”
Section: Introductionmentioning
confidence: 99%
“…However, fluorinated fluoroalkyl groups with shorter side chains are less crystalline, and thus exhibit higher surface molecular mobility. 35,38,39 Consequently, carbonyl groups (-COO-), which are polar groups in fluoroalkyl groups, are exposed on the surface when in contact with water. 35,36 It has been reported that copolymers with fluorinated monomers and alkyl acrylate monomers prepared to suppress the surface molecular mobility of fluoroalkyl groups improve the water repellency of polymeric substrates.…”
mentioning
confidence: 99%
“…The resulting surface resembles a liquid-like layer with nanoscopic thickness. This strategy involves poly­(dimethylsiloxane) (PDMS), alkylchlorosilanes, and perfluorinated polyether covalently grafted to the surface for high repellency against liquids with a broad range of surface tension. The high mobility of these flexible chains allows them to act as a liquid-like lubricating layer against other liquids. , Being only a few nanometers in thickness, the grafted layers exhibit low or no light scattering, rendering them transparent and preserving the appearance of the coated surfaces. ,, Therefore, this strategy is increasingly becoming the choice for many groups to prepare liquid-repellent coatings. ,, Due to their covalent grafting to the substrate, the grafted layers exhibit excellent resistance to mechanical abrasion and are not easily affected by contact with liquids. However, the time-consuming preparation procedures, specific application methods such as vacuum systems, and the use of chemicals such as acids in the fabrication process limit the utilization of liquid-like surfaces in practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…2,24−28 Being only a few nanometers in thickness, the grafted layers exhibit low or no light scattering, rendering them transparent and preserving the appearance of the coated surfaces. 18,29,30 Therefore, this strategy is increasingly becoming the choice for many groups to prepare liquid-repellent coatings. 17,19,31−36 mechanical abrasion and are not easily affected by contact with liquids.…”
Section: ■ Introductionmentioning
confidence: 99%